Reproduction performance of female Nile tilapia under different environments and age classes - Grazyella Massako Yoshida; Carlos Antonio Lopes de Oliveira; Natalí Miwa Kunita; Gabriel Soriani Rizzato; Ricardo Pereira Ribeiro (Acta Scientiarum. Animal Sciences, 2015)
Current assay verifies the reproductive performance of females of Nile tilapia in different age classes and reproductive environments. Four hundred and fifty-one females were evaluated in two different Brazilian environments, namely in Maringá, Paraná State, Brazil (Site 1 - hapas of 10 m3 and Site 2 - hapas of 1 m3) and in one environment in Alfenas, Minas Gerais State, Brazil (Site 3 – hapas of 14 and 28 m3). The females were divided into three age classes, corresponding to animals under one year (age 1); between one to two years (age 2); and over three years old (age 3). Spawning was verified once a week, from October 2012 to March 2013, corresponding to a 23-week assessment. The statistical analyses were performed with Proc Genmod from the statistical program SAS. Site 2 had the lowest results when compared to the other sites for multiple spawning, spawning frequency and volume of eggs/female for animals of age 2. Statistical differences were not detected between ages 1 and 2 for the same assessment site, although females at age 3 in Site 3 provided higher results than those at age 2. Results show that, precluding the use of animals in individual hapas (1 m³) and maintaining older females in the stock, may improve reproduction results.